N-sulfonyl peptide-hybrids as a new class of dengue virus protease inhibitors - Behrouz, Somayeh; Kühl, Nikos; Klein, Christian D. (European journal of medicinal chemistry, 2023)
Dengue virus (DENV) from the Flaviviridae family causes an epidemic disease that seriously threatens human life. The viral serine protease NS2B-NS3 is a promising target for drug development against DENV and other flaviviruses. We here report the design, synthesis, and in-vitro characterization of potent peptidic inhibitors of DENV protease with a sulfonyl moiety as N-terminal cap, thereby creating sulfonamide-peptide hybrids. The in-vitro target affinities of some synthesized compounds were in the nanomolar range, with the most promising derivative reaching a Ki value of 78 nM against DENV-2 protease. The synthesized compounds did not have relevant off-target activity nor cytotoxicity. The metabolic stability of compounds against rat liver microsomes and pancreatic enzymes was remarkable. In general, the integration of sulfonamide moieties at the N-terminus of peptidic inhibitors proved to be a promising and attractive strategy for further drug development against DENV infections.